Minimal residual disease assessment by multiparameter flow cytometry in transplant-eligible myeloma in the EMN02/HOVON 95 MM trial - Oliva, Stefania; Bruinink, Davine Hofste Op; Rihova, Lucie; D'Agostino, Mattia; Pantani, Lucia; Capra, Andrea; van der Holt, Bronno; Troia, Rossella; Petrucci, Maria Teresa; Villanova, Tania; Vsianska, Pavla; Jugooa, Romana; et al. (Blood cancer journal, 2021)
Minimal residual disease (MRD) by multiparameter flow cytometry (MFC) is the most effective tool to define a deep response in multiple myeloma (MM). We conducted an MRD correlative study of the EMN02/HO95 MM phase III trial in newly diagnosed MM patients achieving a suspected complete response before maintenance and every 6 months during maintenance. Patients received high-dose melphalan (HDM) versus bortezomib-melphalan-prednisone (VMP) intensification, followed by bortezomib-lenalidomide-dexamethasone (VRd) versus no consolidation, and lenalidomide maintenance. Bone marrow (BM) samples were processed in three European laboratories, applying EuroFlow-based MFC protocols (eight colors, two tubes) with 10-4-10-5 sensitivity. At enrollment in the MRD correlative study, 76% (244/321) of patients were MRD-negative. In the intention-to-treat analysis, after a median follow-up of 75 months, 5-year progression-free survival was 66% in MRD-negative versus 31% in MRD-positive patients (HR 0.39; p < 0.001), 5-year overall survival was 86% versus 69%, respectively (HR 0.41; p < 0.001). MRD negativity was associated with reduced risk of progression or death in all subgroups, including ISS-III (HR 0.37) and high-risk fluorescence in situ hybridization (FISH) patients (HR 0.38;). In the 1-year maintenance MRD population, 42% of MRD-positive patients at pre-maintenance became MRD-negative after lenalidomide exposure. In conclusion, MRD by MFC is a strong prognostic factor. Lenalidomide maintenance further improved MRD-negativity rate.
Keywords: reziduální nádor; průtoková cytometrie; Multiple Myeloma; Bortezomib; Middle Aged; Neoplasm, Residual; mužské pohlaví; míra přežití; buňky kostní dřeně; Flow Cytometry; Lenalidomide; Melphalan; Hematopoietic Stem Cell Transplantation; mnohočetný myelom; Disease-Free Survival; ženské pohlaví; bortezomib; transplantace hematopoetických kmenových buněk; Humans; Autografts; dexamethason; melfalan; Bone Marrow Cells; Survival Rate; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Dexamethasone; autologní štěp; Female; lenalidomid; přežití bez známek nemoci; lidé; Male